Schistosoma Tegument Proteins in Vaccine and Diagnosis Development: An Update - Cristina Toscano Fonseca; Gardênia Braz Figueiredo Carvalho; Clarice Carvalho Alves; Tatiane Teixeira de Melo (Journal of Parasitology Research)
The development of a vaccine against schistosomiasis and also the availability of a more sensitive diagnosis test are important tools to help chemotherapy in controlling disease transmission. Bioinformatics tools, together with the access to parasite genome, published recently, should help generate new knowledge on parasite biology and search for new vaccines or therapeutic targets and antigens to be used in the disease diagnosis. Parasite surface proteins, especially those expressed in schistosomula tegument, represent interesting targets to be used in vaccine formulations and in the diagnosis of early infections, since the tegument represents the interface between host and parasite and its molecules are responsible for essential functions to parasite survival. In this paper we will present the advances in the development of vaccines and diagnosis tests achieved with the use of the information from schistosome genome focused on parasite tegument as a source for antigens.